TMEM123 a key player in immune surveillance of colorectal cancer - Pesce, Elisa; Cordiglieri, Chiara; Bombaci, Mauro; Eppenberger-Castori, Serenella; Oliveto, Stefania; Manara, Cristina; Crosti, Mariacristina; Ercan, Caner; Coto, Mairene; Gobbini, Andrea; Campagnoli, Susanna; Donnarumma, Tiziano; et al. (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is a leading cause of cancer-associated death. In the tumor site, the interplay between effector immune cells and cancer cells determine the balance between tumor elimination or outgrowth. We discovered that the protein TMEM123 is over-expressed in tumour-infiltrating CD4 and CD8 T lymphocytes and it contributes to their effector phenotype. The presence of infiltrating TMEM123+ CD8+ T cells is associated with better overall and metastasis-free survival. TMEM123 localizes in the protrusions of infiltrating T cells, it contributes to lymphocyte migration and cytoskeleton organization. TMEM123 silencing modulates the underlying signaling pathways dependent on the cytoskeletal regulator WASP and the Arp2/3 actin nucleation complex, which are required for synaptic force exertion. Using tumoroid-lymphocyte co-culture assays, we found that lymphocytes form clusters through TMEM123, anchoring to cancer cells and contributing to their killing. We propose an active role for TMEM123 in the anti-cancer activity of T cells within tumour microenvironment.